Interaction Between Zn Deficiency, Toxicity and Turnip Yellow Mosaic Virus Infection in Noccaea ochroleucum - Morina, Filis; Mishra, Archana; Mijovilovich, Ana; Matoušková, Šárka; Brückner, Dennis; Špak, Josef; Küpper, Hendrik (Frontiers in Plant Science, 2020)
Zinc is essential for the functioning of numerous proteins in plants. To investigate how Zn homeostasis interacts with virus infection, Zn-tolerant Noccaea ochroleucum plants exposed to deficient (Zn’0’), optimal (Zn10), and excess Zn (Zn100) concentrations, as well as Cd amendment, were infected with Turnip yellow mosaic virus (TYMV). Imaging analysis of fluorescence kinetics from the μs (OJIP) to the minutes (Kautsky effect, quenching analysis) time domain revealed strong patchiness of systemic virus-induced photosystem II (PSII) inhibition. That was more pronounced in Zn-deficient plants, while Zn excess acted synergistically with TYMV, in both cases resulting in reduced PSII reaction centers. Infected Cd-treated plants, already severely stressed, showed inhibited non-photochemical quenching and PSII activity. Quantitative in situ hybridization at the cellular level showed increased gene expression of ZNT5 and downregulation of HMA4 in infected Zn-deficient leaves. In Zn10 and Zn100 infected leaves, vacuolar sequestration of Zn increased by activation of HMA3 (mesophyll) and MTP1 (epidermis). This correlated with Zn accumulation in the mesophyll and formation of biomineralization dots in the cell wall (Zn100) visible by micro X-ray fluorescence tomography. The study reveals the importance of adequate Zn supply and distribution in the maintenance of photosynthesis under TYMV infection, achieved by tissue-targeted activation of metal transporter gene expression.